Social Informatics 8th International Conference, SocInfo 2016, Bellevue, WA, USA, November 11-14, 2016, Proceedings, Part I - Spiro, Emma; Ahn, Yong-Yeol (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2016)
The two-volume set LNCS 10046 and 10047 constitutes the proceedings of the 8th International Conference on Social Informatics, SocInfo 2016, held in Bellevue, WA, USA, in November 2016. The 36 full papers and 39 poster papers presented in this volume were carefully reviewed and selected from 120 submissions. They are organized in topical sections named: networks, communities, and groups; politics, news, and events; markets, crowds, and consumers; and privacy, health, and well-being.